A 50‐year‐old woman with haemoptysis, cough and tachypnea: cholesterol pneumonia accompanying with pulmonary artery hypertension. (14th July 2015) - Li, Mengxi; Zhang, Nuofu; Zhou, Ying; Li, Jinhui; Gu, Yingying; Wang, Jian; Liu, Chunli
Abstract: Lipoid pneumonia is an uncommon disease caused by the presence of lipid in the alveoli. Here we described a case of a 50‐year‐old woman with haemoptysis, cough and tachypnea, who was diagnosed with cholesterol pneumonia accompanying with pulmonary artery hypertension. The extremely high pulmonary artery pressure achieved, in this case, is alarming and should alert the physicians that the cholesterol pneumonia may be one of the underlying causes of pulmonary artery hypertension. After a treatment of methylprednisolone, her clinical symptoms were significantly improved, which suggested that steroid might be a promising therapeutic for patients with cholesterol pneumonia.